Economy-wide assessment of potential long-term impacts of the Grand Ethiopian Renaissance Dam on Sudan. Issue 3 (3rd April 2021) - Siddig, Khalid; Basheer, Mohammed; Luckmann, Jonas
ABSTRACT: The Grand Ethiopian Renaissance Dam (GERD) is expected to double Ethiopia's electricity generation and impact River Nile flows to Sudan and Egypt. We analyse potential economy-wide impacts on Sudan of the GERD's long-term operation using a computable general equilibrium model and outputs of previous studies from biophysical models. Based on a 20% increase in hydropower and an assumed rapid irrigation expansion timeline, the results show that the GERD could help increase Sudan's accumulated gross domestic product (GDP) by US47-83 billion over the period 2020-60 (excluding initial investment costs and other GERD negative and positive impacts). The choice of crops in new irrigation schemes is key to increasing Sudan's macro-economic benefits.